2001
DOI: 10.1128/jvi.75.20.9947-9954.2001
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence of the Functional Epitopes of Poxvirus and Human Interleukin-18-Binding Proteins

Abstract: Molluscum contagiosum virus, a human poxvirus that causes persistent small benign skin tumors, encodes a variety of putative immune defense proteins. Three such proteins, MC51L, MC53L, and MC54L, have 20 to 35% amino acid sequence identities with human interleukin-18 (hIL-18)-binding protein (hIL-18BP), a naturally occurring antagonist of the proinflammatory cytokine IL-18. We previously demonstrated that seven amino acids within the immunoglobulin-like domain of hIL-18BP were important for high-affinity bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 39 publications
1
57
0
1
Order By: Relevance
“…Lys-53 also forms a hydrogen bond and a salt bridge, respectively, with Glu-69 and Glu-77 of ectvIL-18BP, effectively lodging hIL-18 Lys-53 into a remarkably secure position. These intimate interactions form a network of stabilizing forces at binding site A, fully explaining some previous mutagenesis studies on various IL-18BPs and hIL-18 (14)(15)(16)(17). These studies identified Tyr-53 and Phe-67 of ectvIL-18BP and Lys-53 of hIL-18 as residues that contribute most significantly to complex formation between these 2 molecules.…”
Section: Resultssupporting
confidence: 56%
“…Lys-53 also forms a hydrogen bond and a salt bridge, respectively, with Glu-69 and Glu-77 of ectvIL-18BP, effectively lodging hIL-18 Lys-53 into a remarkably secure position. These intimate interactions form a network of stabilizing forces at binding site A, fully explaining some previous mutagenesis studies on various IL-18BPs and hIL-18 (14)(15)(16)(17). These studies identified Tyr-53 and Phe-67 of ectvIL-18BP and Lys-53 of hIL-18 as residues that contribute most significantly to complex formation between these 2 molecules.…”
Section: Resultssupporting
confidence: 56%
“…IL-18-induced cellular activation is counteracted by the IL-18 binding protein (IL-18BP), a natural occurring antagonist that binds IL-18 with very high affinity [34]. Interestingly, a similar binding has been reported for viral IL-18BP homologs that are encoded by poxviruses such as Molluscum contagiosum virus (MCV) and represent a mechanism of escape from the immune response [35,36]. Thus, similar to IL-1β, the balance between IL-18 and its antagonist dictates the role of the cytokine in both health and disease.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, it is likely that the alternate splicing, leading to the generation of D3pro-IL-18, may represent a regulatory mechanism that inhibits the production of biologically active IL-18 in some ovarian tumors. In this context, it should be outlined that similar to the IL-1b/IL-1R system, the IL-18/IL-18R system also has several natural inhibitors which may negatively regulate the IL-18 biological activity, protecting the organism from unappropriate IL-18-mediated damage (Novick et al, 1999;Kim et al, 2000;Young et al, 2000;Xiang and Moss, 2001;Bufler et al, 2002). Thus, a soluble IL-18 binding protein (BP), which prevent binding of mature IL-18 to its receptor, and inhibits IL-18 biological activity has been identified Figure 6 D3pro-IL-18 binds to caspase-1.…”
Section: Discussionmentioning
confidence: 99%
“…1 mg of rabbit Ig was run in a control lane Caspase-1 and -4-resistant variant of pro-IL-18 A Gaggero et al (Novick et al, 1999). Four isoforms of this IL-18 BP, displaying differential ability to bind and inhibit IL-18 activity exists in humans (Kim et al, 2000), and a poxvirus-encoded IL-18 BP analog displaying similar inhibitory activity has been described (Xiang and Moss, 2001). In addition, a IL-1b homologue (IL-1F7b) has been reported to interact with IL-18 BP and cooperate in blocking IL-18 activity (Bufler et al, 2002).…”
Section: Discussionmentioning
confidence: 99%